Effects of sintering temperature and addition of Fe and B₄C on hardness and wear resistance of diamond reinforced metal matrix composites - Şimşir, M.; Öksüz, K.E. (Сверхтвердые материалы, 2013)
The effects of sintering temperature and addition of Fe instead of Co into the matrix composition on the mechanical properties of diamond-reinforced MMC’s have been studied. Diamond-reinforced MMC’s based on Fe–Co compositions with and without boron carbide (B₄C) have been processed. Three different matrix composites (with different Fe/Co ratios) have been produced with and without B₄C at a pressure of 25 MPa and sintered in N2 at various temperatures (800, 900, and 1000°C). After sintering, mechanical properties of the resultant composites have been studied and the results discussed. Addition of B₄C has been found to improve the hardness and wear resistance of the composites. Optical microscopy, SEM and EDS have been used to examine the microstructure and surface of the synthesized composites.